Microsoft Project 2010 step by step - Chatfield, Carl S., 1964-; Johnson, Timothy D., 1962- (Step by step (Redmond, Wash.), 2010)
Microsoft Project 2010 offers flexibility and choice for individuals, teams, and the enterprise to effectively manage all types of work - from simple tasks to complex projects and programs.